2020
DOI: 10.1097/pcc.0000000000002388
|View full text |Cite
|
Sign up to set email alerts
|

Fathers of Children With Congenital Heart Disease: Sources of Stress and Opportunities for Intervention

Abstract: Objective: To examine sources of stress for fathers of children with congenital heart disease (CHD) and opportunities for intervention to prevent or reduce paternal mental health problems.Design: Qualitative study using online crowdsourcing, an innovative research methodology to create an online community to serve as a research sample.Setting: Yammer, an online social networking site.Subjects: Geographically diverse sample of 70 parents (25 fathers and 45 mothers) of young children with CHD. Interventions:Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…A prior evaluation of this cohort found that both mothers and fathers of children with CHD desire formalized peer support during and after hospitalization even when they did not receive it themselves (Gramszlo et al, 2020). In addition, fathers describe unique sources of stress, highlighting a lack of formal and informal opportunities for social support for fathers as one such stressor (Hoffman et al, 2020). A recent meta‐analysis examining published mental health interventions for parents of infants with CHD noted that only two studies recruited fathers for the intervention, whereas only one of these studies included paternal outcome data (Kasparian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A prior evaluation of this cohort found that both mothers and fathers of children with CHD desire formalized peer support during and after hospitalization even when they did not receive it themselves (Gramszlo et al, 2020). In addition, fathers describe unique sources of stress, highlighting a lack of formal and informal opportunities for social support for fathers as one such stressor (Hoffman et al, 2020). A recent meta‐analysis examining published mental health interventions for parents of infants with CHD noted that only two studies recruited fathers for the intervention, whereas only one of these studies included paternal outcome data (Kasparian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 As families brace for the impact of congenital heart disease, both mothers and fathers are psychologically affected at the onset of the fetal diagnosis to post cardiac programmes. 14,17,18,25 Further, the amount of stress significantly increases with this diagnosis, and parents report greater stress, anxiety, trauma, and depression relative to the general population. 20,21,26,27 Research has demonstrated the efficacy of psychological interventions implemented during pregnancy in reducing maternal anxiety, depression, and stress, 19,[28][29][30] but very few trials have included pregnant women receiving fetal cardiac diagnoses 31 even though studies assessing prenatal counselling and pre-surgery education have supported a reduction in parental anxiety.…”
Section: Introductionmentioning
confidence: 92%
“…Second, our sample only included mothers, not fathers nor same-sex partners, which will be important for future studies to consider as past studies have demonstrated fathers too experience significant distress and emotional strain during this vulnerable time. 25,37 Third, our sample included more mothers with a child diagnosed with congenital heart disease than pregnant mothers. This is an important factor to consider given information regarding emotions, coping mechanisms, and thoughts at time of pregnancy were provided to us retrospectively.…”
Section: Themementioning
confidence: 99%
“…Parents can be supported to help strengthen core life skills including parenting, self-regulation, and executive function [ 163 ]. Elucidating sources of stress for parents and children including stressors at home, e.g., finances, food security, and domestic violence, can help inform strategies to reduce stress and improve coping [ 164 , 165 , 166 ].…”
Section: Embracing Neuroscience In the Picumentioning
confidence: 99%